2004
DOI: 10.1200/jco.2004.08.127
|View full text |Cite
|
Sign up to set email alerts
|

Papillary and Follicular Thyroid Carcinomas Show Distinctly Different Microarray Expression Profiles and Can Be Distinguished by a Minimum of Five Genes

Abstract: PTC and FTC show distinctive microarray expression profiles, suggesting that either they have different molecular origins or they diverge distinctly from a common origin. Furthermore, if verified in a larger series of tumors, these genes could, in combination with known tumor-specific chromosome translocations, form the basis of a valuable diagnostic tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
85
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(92 citation statements)
references
References 23 publications
6
85
0
1
Order By: Relevance
“…Decreased caveolin expression has previously been observed in Tg-A2aR mice (Goffard et al, 2004) and has also been shown to be a characteristic of thyroid follicular carcinomas (Aldred et al, 2003(Aldred et al, , 2004. The decreased expression in autonomous adenomas, which are benign, noninvading tumors, certainly shows that, as for N-cadherin overexpression, underexpression of caveolins is not sufficient to confer a malignant phenotype and is not even a marker of malignancy.…”
Section: Discussionmentioning
confidence: 86%
“…Decreased caveolin expression has previously been observed in Tg-A2aR mice (Goffard et al, 2004) and has also been shown to be a characteristic of thyroid follicular carcinomas (Aldred et al, 2003(Aldred et al, , 2004. The decreased expression in autonomous adenomas, which are benign, noninvading tumors, certainly shows that, as for N-cadherin overexpression, underexpression of caveolins is not sufficient to confer a malignant phenotype and is not even a marker of malignancy.…”
Section: Discussionmentioning
confidence: 86%
“…Genes regulated in a similar direction in cultured thyrocytes and autonomous adenomas, but that are regulated in the inverse way in papillary carcinomas, might reflect the differentiating action of the TSH-cAMP pathway [DIO2 (26,37), HGD (38), FHL1 (39), ITPR1 (39,40), CRABP1 (40,41), and ADM (40)], whereas common expression in the TSH-stimulated thyrocytes, autonomous adenomas, and papillary carcinomas concerns possibly proteins involved in the control or support of cell growth [EFHD2, IER2, KLF6 (10), EGR1 (10), GADD45B, and JUN]. One puzzling common property of autonomous adenomas and papillary carcinomas is the down-regulation of a number of immediate early genes [NR4A1, JUNB (10), KLF10, and ZFP36].…”
Section: Discussionmentioning
confidence: 99%
“…Genomic and proteomic molecular profiling is providing new insights into cancer by revealing distinctive gene expression patterns associated with a wide variety of molecular and clinical parameters (Hanash, 2004). These approaches are beginning to be applied to thyroid cancer (Huang et al, 2001;Barden et al, 2003;Aldred et al, 2004;Chevillard et al, 2004;Finley et al, 2004;Frattini et al, 2004;Hawthorn et al, 2004;Mazzanti et al, 2004;Wreesmann et al, 2004) and should yield significant improvements in thyroid cancer diagnosis, prognosis and treatment.…”
Section: Introductionmentioning
confidence: 99%